2019
DOI: 10.1038/s41467-019-11703-x
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-deposited zeolitic imidazolate frameworks as gap-filling ultra-low-k dielectrics

Abstract: The performance of modern chips is strongly related to the multi-layer interconnect structure that interfaces the semiconductor layer with the outside world. The resulting demand to continuously reduce the k-value of the dielectric in these interconnects creates multiple integration challenges and encourages the search for novel materials. Here we report a strategy for the integration of metal-organic frameworks (MOFs) as gap-filling low-k dielectrics in advanced on-chip interconnects. The method relies on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 130 publications
(139 citation statements)
references
References 97 publications
1
124
0
Order By: Relevance
“…While the liquid phase approaches discussed earlier are very attractive, the use of liquid solvents is still a drawback for some applications in digital and information technologies, where thin films are used as dielectrics, barrier layers, and capacitors. 45,46 MOF thin films have become an engaging alternative to the existing materials used in the microelectronics industry because in addition to displaying electric conductivity, wide dielectric constants, and high breakdown voltage, they are also recognised for their selective molecular sensing and tuneable dielectric properties. 5 As in the case of conventional materials found in electronic devices, MOF thin films have currently been grown through a combination of well-established gas phase techniques such as physical vapour deposition (PVD, i.e.…”
Section: Gas Phase Approachesmentioning
confidence: 99%
“…While the liquid phase approaches discussed earlier are very attractive, the use of liquid solvents is still a drawback for some applications in digital and information technologies, where thin films are used as dielectrics, barrier layers, and capacitors. 45,46 MOF thin films have become an engaging alternative to the existing materials used in the microelectronics industry because in addition to displaying electric conductivity, wide dielectric constants, and high breakdown voltage, they are also recognised for their selective molecular sensing and tuneable dielectric properties. 5 As in the case of conventional materials found in electronic devices, MOF thin films have currently been grown through a combination of well-established gas phase techniques such as physical vapour deposition (PVD, i.e.…”
Section: Gas Phase Approachesmentioning
confidence: 99%
“…[14] They also found that this conversion of ZnO to ZIF-8 can occur not only on a flat surface, but also on various patterned surfaces, which could contribute to applying MOFs in the semiconductor industry. [8,14] Specifically, as indicated in Figure 2b and c, ZIF-8 films can be grown on selected areas by lifting-off a patterned photoresist, and it is even possible to be directly coated on patterned soft materials (e. g., polydimethylsiloxane (PDMS) pillars). This growth method has been further utilized for the growth of the MAF-6 thin film which is composed of Zn 2 + cations and 2-ethylimidazole molecules instead of 2-mIm in ZIF-8.…”
Section: Cvd-based Gas-phase Mof Thin Film Growthmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) consist of inorganic metal cation building units and organic linkers, which can form longrange ordered highly porous structures. [1] Thin films of MOFs have been widely studied because the chemical and structural characteristics of MOFs can be applied in drug delivery, microporous membranes, and microelectronic devices (e. g., gas sensors, [2][3][4][5][6] low-k dielectrics, [7][8][9] other electronic & opto-electronic devices). [11][12][13] Additionally, cobalt-based MOF layers coated on carbon cloths showed impressive catalytic activity for water splitting recently, which shows the potential of MOF thin films as catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, MOF chemical vapor deposition (MOF‐CVD) was inspired by OSFR chemistry . The MOF‐CVD approach relies on two steps: vapor‐phase deposition of an oxide precursor followed by its reaction with the vaporized linker , . Recently, we developed CVD protocols for the microporous zinc 2‐methylimidazolate {[Zn(mIm) 2 ]} MAF‐4 (also known as ZIF‐8) and mesoporous zinc 2‐ethylimidazolate {[Zn(eIm) 2 ]} MAF‐6 , .…”
Section: Introductionmentioning
confidence: 99%